Staying Connected: A Conversation With Sheldon Braaten. (January 2016) - Zabel, Robert; Kaff, Marilyn; Teagarden, Jim
Sheldon Braaten career has focused on children and youth with significant behavior and emotional challenges. His career has spanned experiences from a mental health therapist, special education teacher, school administrator, and university professor. Sheldon founded the Behavioral Institute for Children and Adolescents and initiated the International Child and Adolescent conference. He is an established author and editor in the field and was the recipient of the Howard Muscott CCBD Distinguished Service Award in 2013 from the Council for Children with Behavioral Disorders. Dr. Braaten shared his reflections with members of the JANUS project shortly after receiving this service award. Sheldon describes the benefit of establishing and nourishing connections for a successful and rewarding career.